Towards the interaction between large solutes in a fluid of small hard spheres - Henderson, D.; Wasan, D.T.; Trokhymchuk, A. (Condensed Matter Physics, 2001)
The equivalence of the asymptotic expression for the interaction energy
between a pair of large hard spheres in a fluid of small hard spheres that
has been obtained by Roth et al. [Phys. Rev. E, 2000, vol. 62, p. 5360] using
Fourier transforms and an expression that we have obtained [J. Colloid Int.
Sci., 1999, vol. 210, p. 320] using Laplace transforms is pointed out and
commented upon. Вказано і прокоментовано еквівалентність асимптотичного виразу
для енергії взаємодії між парою великих твердих сфер у флюїді малих
твердих сфер, який був отриманий Росом та ін. [Phys. Rev. E, 2000,
том 62, с. 5360], використовуючи Фур’є перетворення і виразу, який
ми отримали [J. Colloid Int. Sci., 1999, том 210, с. 320], використовуючи перетворення Лапласа.